Pajak, Tunneling Incentive, Nilai Tukar dan Keputusan Transfer Pricing - Jayanti, Kadek Karya Dwi; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2023)
The research aims to find out and empirically test the effect of taxes, tunneling incentives and exchange rates on transfer pricing carried out in manufacturing companies listed on the Indonesia Stock Exchange (IDX). Sampling method with purposive sampling method. The sample of this research were 20 companies with an observation period of 3 years so that 60 samples were obtained. Collecting data using the non-participant observation method by downloading the financial statements of manufacturing companies listed on the IDX. The data analysis technique is logistic regression analysis. The results of the study show that taxes have a positive effect on the company's decision to transfer pricing. Meanwhile, tunneling incentives and exchange rates have no effect on the company's decision to carry out transfer pricing. Keywords: Tax; Tunneling Incentive; Exchange Rate; Transfer Pricing